ANALISIS PENDAPATAN DAN TATANIAGA BERAS VARIETAS PANDAN WANGI DAN VARIETAS UNGGUL BARU - Yunita, Ima; Yusdiarti, Arti; Nahraeni, Wini (Universitas Djuanda, 2015)
ABSTRACTThe purpose of this research is to determine the pandan wangi rice and new prime varieties rice farmer’s income, the marketing channel, the marketing margin, the farmer's share, as well as the ratio of benefits and costs. The results showed that pandan wangi rice farmer’s income per season is more than the farmers of the new prime varieties rice, while the pandan wangi varieties farmer’s income per year less than the new prime varieties rice farmers. There are 5 channels ofpandan wangi rice marketing, while there are 7 channels of new prime varieties rice marketing. Marketing functions of pandan wangi and the new prime varieties rice differ in the level of collector. The marketing margin, farmer’s share, cost and benefit ratio of pandan wangi rice varieties which have the largest are in the marketing channel 1, 5, and 1. The marketing margin, farmer’s share, cost and benefit ratio of new prime varieties rice which have the smallest valuesare in the marketing channel 5, 1, and 5. The marketing margin, farmer’s share, cost and benefit ratio of the new prime varieties rice that have the largest are in the marketing channels 1, 4, and 7. The marketing margin, farmer’s share, cost and benefit ratio of new prime varieties rice whichhave the smallest values are in the marketing channels 4, 1, and 6Key words: Income, marketing, pandan wangi varieties, new rice varieties